HMGA2 promotes nasopharyngeal carcinoma progression and is associated with tumor resistance and poor prognosis - Ouyang, Xinting; Li, Kangxin; Wang, Jiaqi; Zhu, Weijian; Yi, Qiang; Zhong, Jinghua (Frontiers in Oncology, 2024)
Nasopharyngeal carcinoma (NPC), as one of the most prevalent malignancies in the head and neck region, still lacks a complete understanding of its pathogenesis. Presently, radiotherapy, concurrent chemoradiotherapy, and targeted therapy stand as the primary modalities for treating NPC. With advancements in medicine, the cure rates for nasopharyngeal carcinoma have been steadily increasing. Nevertheless, recurrence and metastasis persist as the primary reasons for treatment failure. Consequently, a profound exploration of the molecular mechanisms underlying the occurrence and progression of nasopharyngeal carcinoma, along with the exploration of corresponding therapeutic approaches, becomes particularly imperative in the quest for comprehensive solutions to combat this disease. High mobility group AT-hook 2 (HMGA2) is a pivotal protein capable of altering chromatin structure, regulating gene expression, and influencing transcriptional activity. In the realm of cancer research, HMGA2 exhibits widespread dysregulation, playing a crucial role in nearly all malignant tumors. It is implicated in various tumorigenic processes, including cell cycle regulation, cell proliferation, epithelial-mesenchymal transition, angiogenesis, tumor invasion, metastasis, and drug resistance. Additionally, HMGA2 serves as a molecular marker and an independent prognostic factor in certain malignancies. Recent studies have increasingly unveiled the critical role of HMGA2 in nasopharyngeal carcinoma (NPC), particularly in promoting malignant progression, correlating with tumor resistance, and serving as an independent adverse prognostic factor. This review focuses on elucidating the oncogenic role of HMGA2 in NPC, suggesting its potential association with chemotherapy resistance in NPC, and proposing its candidacy as an independent factor in nasopharyngeal carcinoma prognosis assessment.